Analisis Aplikasi Sistem Informasi Penatausahaan Perbendaharaan Online (SIPPOL) Berbasis Pada Manajemen Layanan SPBE (Studi Pada Pemerintah Provinsi Jawa Timur) - cahyani, adena mahaya; Gamaputra, Gading (Universitas Negeri Surabaya, 2023)
Research on Analysis of SIPPOL Applications Based on SPBE Service Management (Studies in the East Java Provincial Government) in its implementation there are still several problems, such as SIPPOL application training conducted once via zoom meeting, no SOP when there is a slow SIPPOL application in the BKU input process, no SOP for unlocking data, there is no deadline for SPJ work and there is no guidebook and specific regulations related to the implementation of the SIPPOl Application. using descriptive qualitative method. The research focus is based on SPBE service management indicators in Presidential Decree No. 95 of 2018 concerning SPBE. Data collection techniques with observation, interviews, documentation. Data analysis techniques in the form of data collection, data reduction, data display, data verification. The results showed that the complaint service for SIPPOL application services was less effective, due to the absence of a manual for complaint reporting mechanisms for SIPPOL application services. The service for interruptions/problems with the SIPPOL application service is less effective, because there is no SOP when the SIPPOL application is slow in the BKU input process. Service requests and changes to SIPPOL application services are less effective, because there is no SOP for unlocking data when there is an error in uploading BKU. The utilization of the SIPPOL application infrastructure is less effective, because the powerpoint for using the SIPPOL application is not sufficient to be used as a guide. Utilization of the SIPPOL application infrastructure in the form of training/socialization activities for the application of the SIPPOL application is also less effective. Maintenance of the SIPPOL application infrastructure is effective, it is proven that the SIPPOL application monitoring and evaluation activities are carried out once a month. The development of the SIPPOL application is effective, as evidenced by preparing an account for each user and designing the SIPPOL application according to the needs of the SKPD treasurer. SIPPOL application development is effective, as evidenced by the addition of features/menus that are tailored to the needs of the SKPD treasurer. Keywords: SPBE Service Management, SIPPOL Application, Services.